2008
DOI: 10.1007/s12298-008-0016-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SSR markers associated with seed coat permeability and electrolyte leaching in soybean

Abstract: Seed coat permeability and electrolyte leaching are the important traits that have been negatively associated with seed longevity in soybean. The objective of this study was to use SSR markers to identify genomic regions significantly associated with QTLs controlling seed coat permeability and electrolyte leaching in a segregating F 2 population derived from a cross of Birsa soya-1 x JS 71-05. Parental polymorphism survey using 145 SSR markers identified 21 polymorphic ones, which were used to genotype 153 F 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…SSR primers that were specifically associated with tolerance alleles (Satt 600) and susceptible alleles (Satt 285, Satt 281) identified were considered as good candidate markers for screening soybean germplasm for the identification of tolerance and susceptible genotypes in soybean breeding programmes. The results corroborates the work of Jagadish et al (2013), Singh et al (2008) and Dargahi et al (2014) that identified same SSR markers to have linkage with storability traits in soybean. Hence, these markers are considered good candidate molecular markers for identifying alleles linked with tolerance or susceptibility to storage stress in soybean.…”
Section: Discussionsupporting
confidence: 92%
“…SSR primers that were specifically associated with tolerance alleles (Satt 600) and susceptible alleles (Satt 285, Satt 281) identified were considered as good candidate markers for screening soybean germplasm for the identification of tolerance and susceptible genotypes in soybean breeding programmes. The results corroborates the work of Jagadish et al (2013), Singh et al (2008) and Dargahi et al (2014) that identified same SSR markers to have linkage with storability traits in soybean. Hence, these markers are considered good candidate molecular markers for identifying alleles linked with tolerance or susceptibility to storage stress in soybean.…”
Section: Discussionsupporting
confidence: 92%
“…Negative correlation is reported between seed hardness with 100-seed weight and rate of water uptake in soybean (Hirota et al 2005). Significant MTAs have been reported for seed coat permeability (assessed by rate of water uptake) in other legume crops; such as Singh et al (2008) identified four QTLs associated with seed coat permeability in soybean, of which one (satt281) showed association with EC.…”
Section: Discussionmentioning
confidence: 99%
“…Niu et al (2013) have reported that 100-seed weight is positively influenced by seed size, which is a function of its length, width and thickness. Rate of water uptake by seed is also known to influence seed quality in chickpea (Lamichaney et al 2016), soybean (Singh et al 2008), flax (Saeidi 2008) fababean (Peksen 2007) and cowpea (Peksen et al 2004), which is attributed to embryo damage and subsequently leaching out of electrolytes necessary for the growth and development of embryo. Entry of water into seed during imbibition is regulated by the physical and chemical constituents of seed coat (Lamichaney et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Four ( Satt538 , Satt600 , Satt434 and Satt285 ) independent SSR markers were significantly associated with seed longevity at a distance of 158.63 cM, 75.4 cM, 105 cM and 25.51 cM on chromosomes A2, D1b, H and J, respectively [ 141 ]. The same population was also subjected to seed coat permeability and electrolyte leaching by the same group [ 142 ], where four SSRs ( Satt434 , Satt538 , Satt281 , and Satt598 on chromosomes H, A2, C2, and E, respectively) were associated with seed coat permeability. In addition, SSR Satt281 has been linked to electrolyte leaching on chromosome C2.…”
Section: Genetic Studies In the 21st Centurymentioning
confidence: 99%